2021
DOI: 10.3389/ijph.2021.613057
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Emotion Reaction of Chinese Health Care Workers Varied During COVID-19: A Repeated Cross-Sectional Research

Abstract: Objectives: To examine risk perception and negative emotions during two periods of the COVID-19 and provide plausible intervention points for the psychological aid under a stressful condition.Methods: The current study adopted the repeated cross-sectional research and was participated by a cohort of Chinese HCWs who were assigned to work at the current disease resistance line. The between-group information about gender, profession, and location was collected in the demographic questionnaire. Risk perception qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
6
0
2
Order By: Relevance
“…As a result, HCWs are at a higher risk for depression, anxiety, insomnia, and stress than the general population 34 , 35 , 36 . In addition, consistent with the findings of this study, a large study of Chinese HCWs shows a higher risk of anxiety and depression among nurses [ 37 ]. Moreover, no association between PTSD and social factors such as age and gender among HCWs.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, HCWs are at a higher risk for depression, anxiety, insomnia, and stress than the general population 34 , 35 , 36 . In addition, consistent with the findings of this study, a large study of Chinese HCWs shows a higher risk of anxiety and depression among nurses [ 37 ]. Moreover, no association between PTSD and social factors such as age and gender among HCWs.…”
Section: Discussionsupporting
confidence: 92%
“…Research has shown that RP is positively related to depressive states ( 38 ), and a higher RP concerning COVID-19 is notably associated with less positive or more negative emotions (NE) ( 39 ). NE, such as worry, fear, and anxiety, have been consistently associated with RP and could be significant indicators of RP ( 40 ). Studies have shown that people who perceive more risks also report higher levels of anxiety ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of psychophysical risks, emotional states, and sleep quality remained stable over the course of the repeated survey, and their associations with the variables we were interested in remained consistent. In previous studies, risk perception and a decrease in negative emotions varied with the development of the pandemic [ 15 , 30 , 31 ]. The physical risk of being infected and the psychosocial risk of less family time were perceived at the highest level in each dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire on the MATMs’ risk perception for COVID-19 referred to the risk perception questionnaire of medical staff [ 15 ]. The questionnaire was self-rated and included 12 questions about different dimensions: personal safety risk (three items), physical function risk (three items), occupational exposure risk (one item), psychosocial evaluation risk (three items), organizational risk (one item), and time pressure (one item).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation